2018
DOI: 10.1128/genomea.00574-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing of Two Equine Influenza A(H3N8) Virus Strains Isolated in Kazakhstan

Abstract: Here, we report the complete genome sequencing of strains A/equine/Kostanay/9/2012(H3N8) and A/equine/LKZ/9/2012(H3N8) of the equine influenza virus belonging to Florida sublineage, clade 2. The strains were isolated in 2012 in the northern and southern regions of Kazakhstan, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…These cases underscore the importance of international/transboundary transport of horses as the primary route of spread of EIV, even in vaccinated individuals, to EIV-free countries. Recent widespread outbreaks of EIV either in horses or donkeys have also been well documented in China [ 27 , 29 ], Kazakhstan [ 30 ], and Malaysia [ 12 ]. Although occasional outbreaks of EIV have been reported in South America in the past, there are pointers to a recent surge in the number of cases over the past few years [ 22 ].…”
Section: Recent Outbreaks Of Eivmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases underscore the importance of international/transboundary transport of horses as the primary route of spread of EIV, even in vaccinated individuals, to EIV-free countries. Recent widespread outbreaks of EIV either in horses or donkeys have also been well documented in China [ 27 , 29 ], Kazakhstan [ 30 ], and Malaysia [ 12 ]. Although occasional outbreaks of EIV have been reported in South America in the past, there are pointers to a recent surge in the number of cases over the past few years [ 22 ].…”
Section: Recent Outbreaks Of Eivmentioning
confidence: 99%
“…Contrary to previous studies with other IAV, Quinlivan et al found that, in the case of EIV, the length of the NS1 protein did not correlate with the level of attenuation [ 182 ]. In the EIV strain used in this study, the virus with the shortest NS1 protein [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Eiv Laivs Based On Truncations Of the Viral Ns1 Proteinmentioning
confidence: 99%
“…Recently, genome of two equine influenza strains namely A/equine/Kostanay/9/2012(H3N8) and A/equine/LKZ/9/2012(H3N8) isolated from Kazakhstan was sequenced completely. It was reported that though the isolates were isolated at the same time there was sequence difference at some points indicating the evolution of equine influence (Burashev et al, 2018 ).…”
Section: Epidemiology and Evolutionmentioning
confidence: 99%
“…The characteristic clinical signs of influenza virus infection in equines include high fever, cough, and serous nasal discharge, and abortion may occur in pregnant animals. The signs could precede to pneumonia, enteritis, emphysema and even death in untreated cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%